Dehiscence and prolonged storage of ‘Kerman’ Pistachios: Effects on morphometry and nutraceutical value - Garcia-Moreno, Perla Judith; de la Rosa, Laura Alejandra; Stevens-Barron, Jazmin Cristina; Rodríguez-Ramirez, Roberto; Corral-Diaz, Baltazar; Alvarez-Parrilla, Emilio; Olivas-Aguirre, Francisco Javier; Wall-Medrano, Abraham (Journal of food science and technology, 2021)
‘Kerman’ pistachios (KP; Pistacia vera L.) are an important crop for several countries but their commercial value is diminished by their shell dehiscence status and prolonged storage in popular marketplaces. The aim was to evaluate the independent/synergistic effect of prolonged storage (1–4 year) and dehiscence status (split/unsplit) on KP’s morphometry and chemical composition. Whole nut’s and kernel’s length, width, thickness, surface area, and volume were more affected by dehiscence (split > unsplit; p ≤ 0.01) than storage time; Kernel’s mass, macronutrient composition and tocopherols (T)/tocotrienols (T3) were not much affected by dehiscence but time-trend correlations were observed with macronutrient composition (split/unsplit; ρ = − 0.57–0.42) and T + T3 (unsplit; ρ = 0.81). Specific/total fatty acids were affected by a complex dehiscence × storage time interaction, and they linearly correlated with certain morphometric characteristics (r ≥ 0.6). Shell dehiscence status more than prolonged storage substantially modifies KP’s quality.